Pseudo-doppler aided cancellation of self-interference in full-duplex communications - Zheng, Dongsheng; Yang, Yuli (Frontiers in Signal Processing, 2022)
In this work, a novel scheme is proposed to enhance the self-interference (SI) cancellation in full-duplex communications. Beyond conventional SI cancellation schemes that rely on the SI suppression, our proposed scheme exploits periodic antenna switching to generate the pseudo-Doppler effect, thus completely removing the SI at the fundamental frequency. In this way, the desired signal is readily obtained through a low-pass filter. For the purpose of performance evaluation, the SI cancellation capability is defined as the difference between the output signal-to-interference-plus-noise ratio (SINR) and the input SINR. Theoretical formulations and numerical results validate that our pseudo-Doppler aided scheme has higher SI cancellation capability than the conventional SI suppression schemes. Moreover, the impact of the SI suppression achieved by conventional schemes and the influence of antenna switching timing difference on the practical implementation of the proposed scheme are investigated, to further substantiate the validity of our pseudo-Doppler aided SI cancellation.